Practical issues in slip-resistant bolted connections for steel structures - Georgiev, Tzvetan (Građevinski materijali i konstrukcije, 2025)
The application of slip-resistant bolted connections is necessary to prevent the contribution of slippage due to bolt-hole-diameter clearances in the lateral displacements of high-rise steel-braced frames or other high-rise structures. The safety and reliability of these connections rely on the reliable value of the slip factor in calculations. Despite the clear guidelines provided by European standards for connection design and execution, certain issues frequently arise in current construction practices. In this article, the author investigates two cases he found in his practice. For that reason, an experimental campaign with slip determining tests to annex G of EN 1090-2 is conducted at the University of Architecture, Civil Engineering and Geodesy (UACEG). The problems which are pointed out and investigated are: how a lack of knowledge about the k-class K2 can impact the slip factor test results, and how various surface treatments, such as fabrication errors, impact the slip factor.